2021
DOI: 10.1177/09691413211018253
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of lung cancer screening with low-dose computed tomography in an Iranian high-risk population

Abstract: Objective The results of recent studies have shown that using low-dose computed tomography (LDCT) for screening of lung cancer (LC) improves cancer outcomes. The objective of the current study was to evaluate the cost-effectiveness of LDCT in an Iranian high-risk population. Methods A Markov cohort simulation model with four health states was used to evaluate the cost-effectiveness of LDCT from a healthcare system perspective in the people aged 55–74 who smoked 25 or more cigarettes per day for 10–30 years. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Our study showed better effect than study in Iran, but was not as good as those conducted in New Zealand, United States, and Canada. In the study of Iran, LDCT was implemented every 3 years and the ICER increased from screening versus no screening was about 3,283.83 US dollars per QALY (34). In studies of New Zealand, United States, and Canada, annual screening was recommended and the corresponding ICER was 24,934.84 US dollars (35), 49,200 to 96,700 US dollars (10), and 33,825 US dollars (11) per QALY, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed better effect than study in Iran, but was not as good as those conducted in New Zealand, United States, and Canada. In the study of Iran, LDCT was implemented every 3 years and the ICER increased from screening versus no screening was about 3,283.83 US dollars per QALY (34). In studies of New Zealand, United States, and Canada, annual screening was recommended and the corresponding ICER was 24,934.84 US dollars (35), 49,200 to 96,700 US dollars (10), and 33,825 US dollars (11) per QALY, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 16 (48%) studies present ACERs rather than ICERs [25,30,[39][40][41][42][43][44][45][46][47][48][49][50][51][52]]. An additional 6 (18%) studies estimate ICERs of annual screening without assessment against biennial comparators [28,[32][33][34][35][36].…”
Section: Comparisons and Cost-effectiveness Ratiosmentioning
confidence: 99%
“…Third, risk-stratified screening intervals should be further refined. Despite many studies comparing different screening intervals, only the population as a whole was analyzed, and the focus was on stratification to either annual, biennial, or triennial screening [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%